NAWACITA AND THE LAW ENFORCEMENT OF CIVIL STATE APPARATUS IN CONSTITUTIONAL LAW PERSPECTIVES IN INDONESIA - jawade hafidz (Jurnal Pembaharuan Hukum, 2017)
“Nawacita” and Constitutional Law needs to be a legal approach to make improvements to the legal system, in order to encourage enforcement of the law with justice, then at least have to involve three pillars consisting of: (1) the substantive law (legal substance), which include legislative reform; (2) legal structure (law structure), including human resources law-enforcement officers (human resource), entered in it anyway coordination among law enforcement officers; and (3) the legal culture (legal culture), both culture and public law enforcement officers or citizens in general.Then, constitutional law and can be answered correctly, can be practiced within their Constitutional Act and may be unenforceable government in running the government. The key factor to keep in mind is eliminating ego-sectoral government agencies. Do not stop until the Act, a similar effort was also made to the laws which are in the executive area, such as government regulations, a presidential decree and ministerial regulation